Adenosquamous inflammatory mammary carcinoma in bitch: Can CA 15-3, CRP and LDH improve prognosis? (Research, Society and Development, 2022)
Inflammatory mammary carcinoma (IMC) is characterized by the presence of any subtype of aggressive carcinoma in association with an intense inflammatory reaction, in addition to the presence of tumor emboli. Considering IMC as a type of cancer with chronic inflammation, the complex relationship between inflammation, and alterations in cellular metabolism have highlighted the rationale assessment of cancer antigen 15-3 (CA 15-3), c-reactive protein (CRP), and lactate dehydrogenase (LDH). The present report had the objective to describe a rare case of adenosquamous carcinoma in mammary gland of a 10-year-old bitch, 7 kg, sexually intact, mixed-breed and how CA 15-3, CRP and LHD helped to determinate the clinical presentation of inflammatory carcinoma and the prognosis. Complete clinical staging, cell blood count and renal, and hepatic biochemistry was performed and did not reveal any significant abnormalities. CA 15-3 (9.46 IU/mL), CRP (5.3 mg/L), and LDH (287 U/L) were all above the references values reported by the literature. Although adenosquamous carcinoma of the mammary gland with inflammatory presentation in dogs is rare, the association of serum biomarkers could improve the patient's prognosis evaluation.